Upaya Pencegahan Stunting Ibu Hamil Melalui Kelas Ibu Hamil dan Demo Masak di PKM Alalak Selatan - Renny Aditya; Samuel L Tobing; Ferry Armanza; Halimah Halimah; Brata Tama Unsandy; Noor Aida Ariyani (Universitas Lambung Mangkurat, 2023)
Abstract Stunting in pregnant women is a public health problem. According to the World Health Organization (WHO), the prevalence of stunting worldwide in 2020 is 22.0% or 149.2 million globally. According to WHO data in 2020, the prevalence of stunting in Indonesia is very high at 31.8%, and it ranks 5th in the country with the highest stunting rate. Based on data from the Banjarmasin City Health Centre in 2020, the prevalence of stunting in Banjarmasin City is 5.8% of 14 districts. Alalak Selatan Health Center is a health centre in Banjarmasin City with a stunting prevalence of 33.29%. This figure is above the average for the National, South Kalimantan Province and Banjarmasin City. It is among the five biggest stunting rates out of 26 Community Health Centers in Banjarmasin City. Reducing stunting is still a priority for South Kalimantan to achieve the target of 14% in 2024. The purpose of this service activity is to increase the knowledge and attitudes of pregnant women toward good cooking and take to nutritional intake during pregnancy and to increase the effectiveness of public health programs in preventing stunting in pregnant women through the use of counselling with the media cooking demonstrations as an educational method at the Alalak Selatan Health Center. The method of carrying out the evaluation was through pretest and Posttest questionnaires on 35 pregnant women. The pretest was carried out before the Pregnant Women's class and the Cooking Demonstration at PKM Alalak Selatan, and the Posttest was as follows. The indicators of the success of this activity have been well achieved. All participants who are indicators of success have participated in socialization activities. The results of the pretest and Posttest are 80% already in the good category. Keywords: Stunting, Cooking Demonstration, Pregnant Women, Socialization Abstrak Stunting pada ibu hamil merupakan masalah kesehatan masyarakat. Menurut World Health Organization (WHO) prevalensi stunting di seluruhdunia pada tahun 2020 sebesar 22,0% atau 149,2 juta secara global. Menurut data WHO pada tahun 2020, prevalensi stunting di Indonesia sangattinggi yaitu sebesar 31,8% dan menempati urutan ke-5 negara dengan angka stunting tertinggi. Berdasarkan data dari Dinas Kesehatan KotaBanjarmasin tahun 2020, prevalensi stunting di Kota Banjarmasin sebesar 5,8% dari 14 kabupaten. Puskesmas Alalak Selatan adalah Puskesmasyang ada di Kota Banjarmasin dengan prevalensi stunting 33,29%. Angka tersebut di atas rata-rata Nasional, Provinsi Kalimantan Selatan danKota Banjarmasin serta termasuk 5 terbesar angka stunting dari 26 Puskesmas di Kota Banjarmasin. Penurunan stunting masih menjadi prioritas Kalsel untuk mencapai target 14% di 2024.Tujuan kegiatan pengabdian ini yaitu untuk meningkatkan pengetahuan dan sikap ibu hamil dalammemasak dan memperhatikan asupan gizi selama kehamilan serta meningkatkan efektivitas program kesehatan masyarakat dalam mencegahstunting ibu hamil melalui pemanfaatan penyuluhan dengan media demo masak sebagai metode edukasi di Puskesmas Alalak Selatan. Metode pelaksanaan evaluasi melalui kuisoner pretest dan posttest pada 35 org ibu hamil. Pretest di laksanakan sebelum dilakukan kelas Ibu Hamil dan Demo Masak di PKM Alalak Selatan dan Posttest sesudahnya. Indikator keberhasilan kegiatan ini sudah tercapai dengan baik. Semua peserta yang menjadi indikator keberhasilan sudah mengikuti kegiatan sosialisasi. Hasil pre-test dan post-test yaitu 80% sudah dalam kategori baik.Kata kunci: Stunting, Demo Masak, Ibu Hamil, Sosialisasi